Collaborative Governance in Minimizing Traffic Accidents: Study on the Role of Pentahelix in East Aceh Regency, Indonesia - Sani, Suryana Asrul; Muslim, Muh. Azis (Golden Ratio of Social Science and Education, 2025)
Traffic accidents remain a significant concern, causing high mortality rates and severe injuries, particularly in East Aceh Regency. This study examines the role of collaborative governance through the pentahelix approach in minimizing traffic accidents. The pentahelix model involves government, academia, businesses, communities, and the media in traffic safety management. Using a literature study method, this research identifies key factors contributing to accidents, evaluates the role of various stakeholders, and explores strategies for effective collaboration. The findings highlight structural challenges, resource limitations, and the need for an integrated approach to accident prevention. The study recommends forming inclusive forums, enhancing knowledge sharing, and strengthening stakeholder coordination to improve road safety. A structured collaborative governance model can significantly reduce traffic accidents, especially among minors, ensuring a safer road environment.